Construct and validation of progesterone-responsive luciferase reporter plasmid to detect progestogenic and anti-progestogenic activity (Bangladesh Veterinarian, 2013)
Chemical and immunological analyses used to detect progesterone and its agonists and antagonists are unable to detect biological activities of unknown compounds. The objective of the experiment was to develop a progesterone-responsive reporter plasmid to detect progestogens and anti-progestogens. Progesterone-responsive luciferase reporter plasmid, pGL3-2PRE-TATA, was constructed by inserting two progesterone-response elements (PRE) and the TATA box at the multiple cloning site of pGL3 basic vector. T47D human breast cancer cells were co-transfected with c pGL3-2PRE-TATA and pCH110 plasmid. The transfected cells were exposed to progesterone, anti-progesterone, herb extracts or animal serum to induce the luciferase gene expression. Cells were lysed, and cell lysates were used to measure the luciferase and ?-galactosidase expression level as well as total protein content. Luciferase activity was normalized by ?-galactosidase activity and total protein content. The constructed plasmid was sensitive to progestogens and anti-progestogens in a dose-responsive manner. The pGL3-2PRE-TATA plasmid can be used to detect the progestogenic and anti-progestogenic activity of known and unknown compounds. DOI: http://dx.doi.org/10.3329/bvet.v30i1.16280 Bangl. vet. 2013. Vol. 30, No. 1, 10-19